COVID-19 Lockdown Increased the Risk of Preterm Birth - Lin, Ting-ting; Zhang, Chen; Chen, Lei; Jin, Li; Lin, Xian-hua; Pan, Jie-xue; Dennis, Cindy-Lee; Mol, Ben W.; Huang, He-feng; Wu, Yan-ting (Frontiers in Medicine, 2021)
Purpose: To estimate whether the city-specific lockdown in Shanghai induced by the COVID-19 pandemic affected preterm birth rates among uninfected pregnant women in different trimesters. Methods: The population-based retrospective cohort study was conducted in the International Peace Maternity and Child Health Hospital (IPMCH) in Shanghai, China. Pregnant women without COVID-19 received perinatal healthcare during lockdown (from January 24, 2020 to March 24, 2020) and non-lockdown (from January 24, 2019 to March 24, 2019) period and giving birth to a live infant at IPMCH were enrolled. 1:1 propensity score matching and Inverse probability of treatment weighting were used to evaluate preterm birth (<37 weeks), very preterm birth (<34 weeks), preterm birth with premature rupture of membranes (PROM-PTB), spontaneous preterm birth with intact membranes (S-PTB), and medically induced preterm birth (MI-PTB) between two groups. Results: 8270 pregnant women were in the lockdown group, and 9815 were in the non-lockdown group. Pregnant women in second trimester during lockdown had a higher risk of PTB than those during the non-lockdown period (OR: 1.43 [CI 1.01–2.02], ARD: 1.7% [CI 0.04%–3.4%], p=0.045). Furthermore, pregnant women in third trimester during lockdown had a higher risk of PROM-PTB than those during the non-lockdown period (OR: 1.64 [CI 1.09-2.47], ARD: 0.9% [CI 0.2% – 1.6%], p =0.02); no group differences were found related to rates of VPTB, S-PTB or MI-PTB. Conclusion: In this cohort study in China, we found that there was an increased risk in preterm birth for non-infected women in COVID-19 lockdown who were in their second trimester.